Fate of Neural Progenitor Cells Transplanted into Jaundiced and Nonjaundiced Rat Brains. Issue 4 (April 2017) - Yang, Fu-Chen; Riordan, Sean M.; Winter, Michelle; Gan, Li; Smith, Peter G.; Vivian, Jay L.; Shapiro, Steven M.; Stanford, John A.
High levels of bilirubin in infants can cause kernicterus, which includes basal ganglia damage and dystonia. Stem cell transplantation may be an effective treatment for this disease. In this study, we transplanted human neural progenitor cells differentiated toward propriospinal interneurons into the striatum of 20-day-old spontaneously jaundiced (jj) Gunn rats and nonjaundiced (Nj) littermates. Using immunohistochemical methods, we found that grafted cells survived and grew fibers in jj and Nj brains 3 weeks after transplantation. Grafted cells had a higher survival rate in jj than in Nj brains, suggesting that slightly elevated bilirubin may protect graft survival due to its antioxidative and immunosuppressive effects. Despite their survival, only a small portion of grafted neurons expressed GAD-6 or ChAT, which mark GABAergic and cholinergic neurons, respectively, and are the cells that we are attempting to replace in kernicterus. Thus, NPCs containing large populations of GABAergic and cholinergic neurons should be used for further study in this field.